Smartphone EEG and remote online interpretation for children with epilepsy in the Republic of Guinea: Quality, characteristics, and practice implications. (October 2019) - Williams, Jennifer A; Cisse, Fodé Abass; Schaekermann, Mike; Sakadi, Foksouna; Tassiou, Nana Rahamatou; Hotan, Gladia C.; Bah, Aissatou Kenda; Hamani, Abdoul Bachir Djibo; Lim, Andrew; Leung, Edward C.W.; Fantaneanu, Tadeu A.; Milligan, Tracey A.; et al.
Highlights: There are limited data on portable EEG technologies in low-income populations. We test a smartphone-based EEG in children with epilepsy compared to standard EEG. 97 children with epilepsy were enrolled in the West African Republic of Guinea. Epileptiform discharges were detected on 25% of smartphone and 37% of standard EEGs. Smartphone EEG had a sensitivity of 52% and specificity of 90% for epileptiform discharges compared to standard EEG. Abstract: Purpose: : Children with epilepsy in low-income countries often go undiagnosed and untreated. We examine a portable, low-cost smartphone-based EEG technology in a heterogeneous pediatric epilepsy cohort in the West African Republic of Guinea. Methods: : Children with epilepsy were recruited at the Ignace Deen Hospital in Conakry, 2017. Participants underwent sequential EEG recordings with an app-based EEG, the Smartphone Brain Scanner-2 (SBS2) and a standard Xltek EEG. Raw EEG data were transmitted via Bluetooth ™ connection to an Android ™ tablet and uploaded for remote EEG specialist review and reporting via a new, secure web-based reading platform, crowdEEG . The results were compared to same-visit Xltek 10–20 EEG recordings for identification of epileptiform and non-epileptiform abnormalities. Results: : 97 children meeting the International League Against Epilepsy's definition of epilepsy (49 male; mean age 10.3 years, 29 untreated with an antiepileptic drug; 0 with a prior EEG) were enrolled. Epileptiform discharges were detected on 21 (25.3%) SBS2 and 31 (37.3%) standard EEG recordings. The SBS2 had a sensitivity of 51.6% (95%CI 32.4%, 70.8%) and a specificity of 90.4% (95%CI 81.4%, 94.4%) for all types of epileptiform discharges, with positive and negative predictive values of 76.2% and 75.8% respectively. For generalized discharges, the SBS2 had a sensitivity of 43.5% with a specificity of 96.2%. Conclusions: : The SBS2 has a moderate sensitivity and high specificity for the detection of epileptiform abnormalities in children with epilepsy in this low-income setting. Use of the SBS2+crowdEEG platform permits specialist input for patients with previously poor access to clinical neurophysiology expertise.